Morphometric Study of Paired and Unpaired Parameters of Axis Vertebra: An Observational Study - Mubashir, SYED; Shahid Kaleem; Mohd saleem itoo; Gh. Mohammad bhat; Javed ahmed khan (International Clinical Neuroscience Journal, 2025)
Background: The axis is the second cervical vertebra and is special in having the upward bony projection from its body called the dens. It functions as the pivot around which the first cervical vertebra rotates. Methods: The present study was observational and conducted in the Department of Anatomy, Government Medical College, Srinagar. The linear and angular parameters were recorded using a manual vernier calliper and goniometer. The vernier calliper’s depth gauge was used to measure the depth of the foramen transversarium. All the identical structures were measured on both sides. The measurements recorded from each vertebra on each axis were analyzed statistically using SPSS Statistics. Results: All the linear paired and unpaired parameters have been recorded using a manual vernier calliper and goniometer. The body’s mean A-P diameter was 15.3±1.76mm, and the transverse diameter was 18.56±1.85mm. The anterior body height was measured at 22.3±1.75mm, and the posterior body height was 17.2±1.55mm. Similarly, the mean height of dens was 15.8±1.77mm, the A-P diameter was 10.7±0.99mm, the maximum width was 10.3mm, and the minimum width was 8.51±0.01 mm. The total height of the dens was 38.1±2.57 mm. Similarly, the dimensions of the pedicle, lateral mass, superior articular facet, inferior articular facet, foramen transversarium, and vertebral foramen were also measured and compared with previous studies. Conclusion: The study will be useful while performing surgical procedures around the axis vertebrae to prevent injury to vital structures.